1988
DOI: 10.1038/331365a0
|View full text |Cite
|
Sign up to set email alerts
|

A highly basic histone H4 domain bound to the sharply bent region of nucleosomal DNA

Abstract: A nucleosomal core particle is composed of two each of histones H2A, H2B, H3 and H4 located inside the particle with approximately 47 base pairs (bp) of DNA wrapped around the octamer in about 1.8 turns of a left-handed superhelix. The path of the superhelix is not smooth; the DNA is sharply bent, or kinked, at positions symmetrically disposed at a distance of about one and four double-helical turns in both directions from the nucleosomal dyad axis (designated as sites +/- 1 and +/- 4 respectively). This non-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(95 citation statements)
references
References 25 publications
5
90
0
Order By: Relevance
“…4), which are very close to the sharply bent regions of the nucleosomal DNA (51-55). Histone H4 cross-links to the sites around Ϯ 1 mainly through the single highly basic domain (30,56,57), which may alter DNA structure in this region (57,58). On the other hand, the change in nucleosomal DNA conformation induced by low ionic strength in isolated core particles or by the stretching of linker DNA during chromatin unfolding can in turn affect histone interactions with these DNA sites.…”
Section: The Change In Histone H2b/h4-dna Contacts Induced By Low Ionmentioning
confidence: 99%
See 1 more Smart Citation
“…4), which are very close to the sharply bent regions of the nucleosomal DNA (51-55). Histone H4 cross-links to the sites around Ϯ 1 mainly through the single highly basic domain (30,56,57), which may alter DNA structure in this region (57,58). On the other hand, the change in nucleosomal DNA conformation induced by low ionic strength in isolated core particles or by the stretching of linker DNA during chromatin unfolding can in turn affect histone interactions with these DNA sites.…”
Section: The Change In Histone H2b/h4-dna Contacts Induced By Low Ionmentioning
confidence: 99%
“…Identification of nucleotide-tagged histone H4 peptides (56,57) and selective proteolysis of cross-linked core particles by trypsin and clostripain (30) have demonstrated that histone H4 cross-links via His-18 to three major sites, at nucleotides 57, 66, and 93, which are extended over 1.2 helical turns of the nucleosomal DNA (Fig. 4).…”
Section: The Change In Histone H2b/h4-dna Contacts Induced By Low Ionmentioning
confidence: 99%
“…The chromatin fiber is organized into loops where the base of the loop (MAR) is attached to nuclear matrix proteins (10,44,45). The chromatin loop may have one or several genes.…”
Section: Chromatin Structure and Histone Modificationsmentioning
confidence: 99%
“…Furthermore all detectable variants of DNA conformation are very sensitive to change of energ y state created by alteration of .the negative supercoiling den sity within a close DNA domain [5] . T here are substantial evidences suggesting that most ( if not all ) DNA-binding reagents ( including proteins) can change conformation of the interacting DNA region directly or indirectly by altering the density of the overall supercoiling of the close DNA domain or molecule [6][7][8].…”
Section: Introductionmentioning
confidence: 99%